4 Ds in health research—working together toward rapid precision medicine - Ellen Niederberger; Michael J Parnham; Jochen Maas; Gerd Geisslinger (EMBO Molecular Medicine)
Abstract Patient therapy is based mainly on a combination of diagnosis, suitable monitoring or support devices and drug treatment and is usually employed for a pre‐existing disease condition. Therapy remains predominantly symptom‐based, although it is increasingly clear that individual treatment is possible and beneficial. However, reasonable precision medicine can only be realized with the coordinated use of diagnostics, devices and drugs in combination with extensive databases (4Ds), an approach that has not yet found sufficient implementation. The practical combination of 4Ds in health care is progressing, but several obstacles still hamper their extended use in precision medicine.